Transcription factor WRKY22 promotes aluminum tolerance via activation of OsFRDL4 expression and enhancement of citrate secretion in rice (Oryza sativa). Issue 1 (15th April 2018) - Li, Ge Zi; Wang, Zhan Qi; Yokosho, Kengo; Ding, Bing; Fan, Wei; Gong, Qiao Qiao; Li, Gui Xin; Wu, Yun Rong; Yang, Jian Li; Ma, Jian Feng; Zheng, Shao Jian
Summary: Whilst WRKY transcription factors are known to be involved in diverse plant responses to biotic stresses, their involvement in abiotic stress tolerance is poorly understood. OsFRDL4, encoding a citrate transporter, has been reported to be regulated by ALUMINUM (Al) RESISTANCE TRANSCRIPTION FACTOR 1 (ART1) in rice, but whether it is also regulated by other transcription factors is unknown. We define the role of OsWRKY22 in response to Al stress in rice by using mutation and transgenic complementation assays, and characterize the regulation of OsFRDL4 by OsWRKY22 via yeas one‐hybrid, electrophoretic mobility shift assay and ChIP‐quantitative PCR. We demonstrate that loss of OsWRKY22 function conferred by the oswrky22 T‐DNA insertion allele causes enhanced sensitivity to Al stress, and a reduction in Al‐induced citrate secretion. We next show that OsWRKY22 is localized in the nucleus, functions as a transcriptional activator and is able to bind to the promoter of OsFRDL4 via W‐box elements. Finally, we find that both OsFRDL4 expression and Al‐induced citrate secretion are significantly lower in art1 oswrky22 double mutants than in the respective single mutants. We conclude that OsWRKY22 promotes Al‐induced increases in OsFRDL4 expression, thus enhancing Al‐induced citrate secretion and Al tolerance in rice.